NORMATIVE LEGAL FRAMEWORK AND PRACTICE OF STATE PLANNING IN RUSSIAN FEDERATION - O. O. Smirnova (Модернизация, инновация, развитие, 2016)
Today, Russia is not secured by the principal – the legal basis for the formation of a unified system of planning and links between federal and regional aspects, and the lack of systematic approach to planning at the state level affects the pace of economic development. Approved are only a few documents regulating work in certain areas of strategic planning, and these documents are often contradictory. Compulsory rules on mandatory components of the strategic, long-term, medium-term, and short-term planning for the country and for regions should be legislatively fixed.